Mizoram Draft Annual Plan 2001-2002 - Planning Commission (Planning Commission, 2001)
Mizoram is one of the youngest States in India attaining the status of Statehood on 20th February. 1987. Mizoram occupies a very strategic position in the North Eastern comer of India having an international boundary of 487.65 Kms and covers an area of 21,081 Sq. Kms. The population of Mizoram as per 1991 Census is 6,89,756 with a density of 33 per Sq. Kms. Literacy as on 31.3.2000 is 96.16% which is the highest in India. The National Highway No. 54 connects Mizoram from Cachar District of Assam. Out of the total 701 villages in Mizoram, 655 villages were connected by road by the end of the 8th Five Year Plan.
Government of Mizoram